(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Acute care surgeons are frequently asked to assess pregnant patients who are experiencing abdominal pain. The majority of diagnostic and treatment choices for pregnant patients will adhere to the standard principles of surgery; nevertheless, pregnant patients have some essential distinctions to be aware of in order to avoid mistakes that could result in difficulties for both mother and fetus. This study aims to outline the most typical emergencies that surgeons dealing with pregnant patients must deal with as well as the most recent treatment choices.